Terminal de transporte fluvial para la región Amazónica (2021)
The Amazon comprises the largest forest area in the world and is one of the largest regions in the country, due to its extreme jungle condition, it has an important parallel, it has an uncountable environmental, cultural and social wealth; but at the same time it faces great challenges such as the connect with the center of the country, the protection of environmental resources and cultural wealth. The intervention site is defined as the "Amazonian trapezoid" because this is where most of the region's population is concentrated and where the two most important population centers are located (Leticia and Puerto Nariño). The proposal as a master plan is based on research from the exploration and studies of the region (flora, fauna and culture) locating the main study nuclei in Puerto Nariño from where a route to the other nuclei located inside the jungle bordering the Amacayacu National Natural Park and is complemented by a proposal for river connectivity at the regional level by the Loretoyacu River and the Amazon to address connectivity issues.